Maternal mortality from puerperal infection in the state of Piauí: an epidemiological study (Research, Society and Development, 2022)
Objective: To analyze the epidemiological profile of maternal mortality due to puerperal infection in the state of Piauí. Methods: This is an epidemiological, retrospective, descriptive study of quantitative character of maternal deaths by puerperal infection between 2016 and 2020, the data were extracted through SIM and SINASC entered in DATASUS. The data was organized by means of graphs and tables for better observation and understanding. The information was compared with the existing scientific literature on the subject. Results: Through the results it can be observed that the year 2019 presented a higher maternal mortality ratio by puerperal infection compared to the other years studied and the municipality that presented the highest MMR was Francisco Ayres in the year 2020. Women aged 20 to 29, single, and with 4 to 7 years of schooling had a higher prevalence of maternal death from puerperal infection. Conclusion: In order to minimize infections, it is essential to establish prophylactic measures such as adequate hygiene for puerperae, as well as for their companions and the health professionals who accompany these women in their pregnancy-puerperium cycle. Thus the prevention, control of diseases, and reduction of maternal morbidity and mortality is achieved.